Comparative GC-MS Analysis of In-House Prepared and Commercial Market Sample of Avartita Guduchi Taila - Sharma, Pankaj; Shukla, Vaibhav; Hemke, Pradnya Prakash; Konkeri, Sonali Dayanand; Dixit, Sanyogeeta Ajay; Shetty, Suhas Kumar (Asian Journal of Biological and Life Sciences, 2026)
Background: Sneha Kalpana (oil formulation), particularly Avartita Guduchi Taila, enhances Guduchi's (Tinospora cordifolia [Willd.] Miers) therapeutic potency through repeated processing. Comparative phytochemical profiling of classically prepared, hundred-times-processed Shatapaka Guduchi Taila (SGT) and the same-time-processed Market Guduchi Taila (MGT) remains unexplored despite their processing similarities. Materials and Methods: Hundred-cycle Avartita SGT was prepared using Guduchi (kalka), Tila Taila (sneha), and Goksheera (drava) as per Ayurvedic Pharmacopoeia standards at a GMP-certified facility. Market-equivalent MGT was procured from a licensed GMP-certified Ayurveda pharmacy (confidentiality maintained). Samples were analysed by GC-MS (DB-5MS column, helium carrier, NIST library ≥85% match). Peaks were normalised to TIC area % for semi-quantitative comparison by retention time alignment. Results: SGT exhibited cholesterol dominance (49.06%, RT 34.292 min) with 12 major peaks. MGT showed diosgenin predominance (12.839%, RT 50.677 min) across 36 peaks. SGT is enriched in antioxidant squalene/phytosterols, while MGT is dominated by steroidal sapogenins (diosgenin, gitogenin). Common fatty acids confirmed processing identity. Conclusion: Distinct phytochemical profiles despite identical Shatapaka processing underscore raw material variability and thermal transformation effects. SGT favors sustained Rasayana/antioxidant action while MGT excels in acute anti-inflammatory/immunomodulation. Findings advocate for processing standardization for consistent Ayurvedic lipid formulations.
Keywords: Avartana; GC-MS Profiling; Phytochemical Comparison; Shatapaka Guduchi Taila